The Effect of Teaching Collocations to Kurdish Tertiary Students through Mobile Learning - Mallampalli, Sasi Sekhar; Goyal, Shriya (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Proficiency in English occupies a significant place in the newly formed Kurdistan region of Iraq. English is considered a window of opportunities and economic development of its people and the region. The quality of teaching and learning plays a crucial role in achieving the objective. However, the lack of trained teachers in English at the school level has severely affected the standards of English at the tertiary level. Students pursuing undergraduate courses at Cihan University find it a challenging task to meet the required standards. The lack of a strong foundation in English in addition to the constraints of time and the high standards of the curriculum at the tertiary level makes it more challenging for the teachers to teach them writing skills. The present study aims at exposing the Kurdish students to English collocations vocabulary through Mobile Assisted Language Learning (MALL) to enhance their writing and communicative purposes. Twenty-five students from undergraduate courses were randomly selected for the purpose of the study. The results have shown an improved performance of the students in using the right collocations. The study brings out the need for integrating MALL in the regular curriculum at the tertiary levels in Kurdistan.